Improving Economic Value Creation of E-Commerce Development Company: Digital Technology Adoption, Business Process Management, And Organizational Agility - Dilshodovna, Rakhimova Madinakhon; Ramdhany, Muhamad Arief (The International Journal of Business Review (The Jobs Review), 2023)
This research aimed to investigate the impact of Digital Technology Adoption on Business Process Management, Organizational Agility, and Economic Value Creation in an e-commerce development company in Uzbekistan. This research utilizes a quantitative approach and a questionnaire as the primary tool to collect data from 42 employees of an e-commerce development company in Uzbekistan. The collected data were analyzed through a comprehensive analysis of data using Partial Least Square (PLS). The results revealed a substantial and positive effect of Digital Technology Adoption on Business Process Management, Organizational Agility, and Economic Value Creation. This impact was influenced not only by direct effects but also through the mediating roles of Business Process Management and Organizational Agility. The implications highlight the strategic importance of embracing digital technology adoption to enhance business process management, organizational agility, and ultimately, economic value creation in the relevant sectors. For the broader e-commerce sector in Uzbekistan, the research provides valuable evidence of the positive impact of digital technologies on organizational outcomes. The novelty of this study lies in its comprehensive examination of the interplay between digital technology adoption, business process management, organizational agility, and economic value creation in the specific context of an e-commerce development company in Uzbekistan, contributing valuable insights to the emerging field of digital transformation in the region